Abiotic-biotic characterization of Pt/Ir microelectrode arrays in chronic implants - Prasad, Abhishek; Xue, Qing-Shan; Dieme, Robert; Sankar, Viswanath; Mayrand, Roxanne; Nishida, Toshikazu; Streit, Wolfgang J.; Sanchez, Justin C. (Frontiers in Neuroengineering, 2014)
Pt/Ir electrodes have been extensively used in neurophysiology research in recent years as they provide more inert recording surface as compared to tungsten or stainless steel. While floating microelectrode arrays consisting of Pt/Ir electrodes are an option for neuroprosthetic applications, long-term in vivo functional performance characterization of these FMAs is lacking. In this study, we have performed comprehensive abiotic-biotic characterization of Pt/Ir arrays in twelve rats with implant periods ranging from one week up to six months. Each of the FMAs consisted of 16-channel, 1.5mm long, and 75µm diameter microwires with tapered tips that were implanted into the somatosensory cortex. Abiotic characterization included (1) pre-implant and post-explant scanning electron microscopy to study recording site changes, insulation delamination and cracking, and (2) chronic in vivo electrode impedance spectroscopy. Biotic characterization included study of microglial responses using a panel of antibodies, such as Iba1, ED1, and anti-ferritin, the latter being indicative of blood-brain barrier disruption. Significant structural variation was observed pre-implantation among the arrays in the form of irregular insulation, cracks in insulation/recording surface, and insulation delamination. We observed delamination and cracking of insulation in almost all electrodes post-implantation. These changes altered the electrochemical surface area of the electrodes and resulted in declining impedance over the long-term due to formation of electrical leakage pathways. In general, the decline in impedance corresponded with poor electrode functional performance, which was quantified via electrode yield. Our abiotic results suggest that manufacturing variability and insulation material as an important factor contributing to electrode failure. Biotic results show that electrode performance was not correlated with microglial activation (neuroinflammation) as we were able to observe poor p